LetMeSpeak Mobile Application Supports Students' English Speaking Skill Development: Aplikasi Mobile LetMeSpeak Dukung Pengembangan Kemampuan Berbahasa Inggris Siswa - Mahendra, Muhammad Fikri Agung; Santoso, Dian Rahma (Indonesian Journal of Education Methods Development, 2025)
General Background: English speaking skills are essential for communication, yet many students struggle with fluency due to limited practice opportunities and ineffective learning methods. Specific Background: In Indonesia, junior high school students often face challenges in vocabulary retention, grammar application, and pronunciation, impacting their speaking proficiency. Knowledge Gap: While technology-enhanced learning tools have shown promise, research on the effectiveness of mobile applications like LetMeSpeak in improving speaking skills remains limited. Aims: This study examines the impact of LetMeSpeak on students' English-speaking skills through a pre-experimental design using pre-test and post-test assessments. Results: The findings reveal a significant improvement in students’ speaking performance, with an average score increase from 62.88 (pre-test) to 76.00 (post-test). Novelty: Unlike traditional methods, LetMeSpeak integrates interactive AI-driven features that enhance pronunciation, vocabulary, and fluency through real-life conversation simulations. Implications: The study suggests that mobile-assisted language learning, particularly LetMeSpeak, can be an effective pedagogical tool for improving English-speaking skills among junior high school students, offering educators an innovative and engaging approach to language instruction. Highlights: Technology-Enhanced Learning – LetMeSpeak effectively improves students' English-speaking skills through interactive AI-driven features. Significant Score Improvement – Students’ average speaking scores increased from 62.88 (pre-test) to 76.00 (post-test). Pedagogical Implications – Mobile-assisted language learning can be a practical tool for enhancing fluency, pronunciation, and vocabulary in junior high school students. Keywords: LetMeSpeak, Speaking Skills, Mobile-Assisted Language Learning, Junior High School, English Education